Parasitic myoma: a rare presentation of a common disease - Aguilar,Sofia (2018)
Parasitic myomas are a rare form of uterine leiomyomas. Distinction from other abdominal masses may be difficult, due to parasitic leiomyomas' variable anatomic locations and clinical manifestations. We describe the case of a 45 years-old woman, presenting with abdominal pain and a large pelvic mass that turned out to be a parasitic myoma at surgical assessment. Histological analysis confirmed the intraoperative suspicion. We intend to bring awareness to the inclusion of this condition in the differential diagnosis of pelvic masses, especially in women with risk factors for parasitic myomas, such as previous surgery for uterine fibromyomatosis or concomitant uterine myomas.